2014
DOI: 10.1038/bmt.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

Specific abnormalities versus number of abnormalities and cytogenetic scoring systems for outcome prediction after allogeneic hematopoietic SCT for myelodysplastic syndromes

Abstract: Newer cytogenetic scoring systems for myelodysplastic syndromes (MDSs), like cytogenetic stratification of the revised international prognostic scoring system (IPSS-R) or monosomal karyotype, may also improve outcome prediction after hematopoietic SCT (HCT). We compared the prognostic value of specific cytogenetic abnormalities, IPSS-R karyotype and monosomal karyotype for HCT outcome in 98 patients with MDS and AML post MDS. Higher-risk IPSS-R karyotype, 3q21q26 and transformation to AML before HCT were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Their strong association with complex karyotypes and higher number of chromosomal alterations might be the expression of an inherent chromosomal instability that facilitates disease progression. Indeed, it is well known that both complex karyotypes and high number of chromosomal alterations confer an adverse prognosis (Morel et al, 1993;Greenberg et al, 1997;Schanz et al, 2012;Kelaidi et al, 2014). A proper prognostic stratification in MDS is essential for designing risk-adapted therapeutic strategies that can range from watchful waiting to allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Their strong association with complex karyotypes and higher number of chromosomal alterations might be the expression of an inherent chromosomal instability that facilitates disease progression. Indeed, it is well known that both complex karyotypes and high number of chromosomal alterations confer an adverse prognosis (Morel et al, 1993;Greenberg et al, 1997;Schanz et al, 2012;Kelaidi et al, 2014). A proper prognostic stratification in MDS is essential for designing risk-adapted therapeutic strategies that can range from watchful waiting to allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging information suggests that disease clones responsible for relapse after HCT often differ from those identified before HCT [15], although the presentation at late relapse is not well defined. We analyzed relapse patterns in 1007 patients who underwent transplantation for MDS in an attempt to identify factors that may determine “early” versus “late” relapse.…”
Section: Introductionmentioning
confidence: 99%
“…But in the study conducted by Schanz et al [13] MK was associated with inferior OS in patients with ≤4 abnormalities only, not in highly complex karyotypes (≥5 abnormalities). In other studies, MK demonstrated negative impact on OS but was not identified as an independent risk factor [14][15][16]. MK is considerably overlapped with complex karyotype (CK, defined as at least three cytogenetic abnormalities).…”
Section: Introductionmentioning
confidence: 88%
“…After carefully reading the full texts, 13 studies were excluded due to insufficient data. Finally, 17 studies, [8][9][10][11][12][13][14][15][16][17][18][19][20][25][26][27][28] including a letter to the editor [18] were included in this meta-analysis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation